Cover Picture: Electrifying White Biotechnology: Engineering and Economic Potential of Electricity‐Driven Bio‐Production (ChemSusChem 5/2015). Issue 5 (20th February 2015) - Harnisch, Falk; Rosa, Luis F. M.; Kracke, Frauke; Virdis, Bernardino; Krömer, Jens O.
<x xml:space="preserve">Abstract</x> The Front Cover picture, drawn by co‐author Frauke Kracke, was inspired by the concept of using electric energy and biomass for the production of fuels and chemicals. It depicts our present society based on fossil fuels, e.g., oil, which are converted into fuels and chemicals in chemical refineries, and a future greener world in which biomass is converted in electro‐bioreactors using energy from renewable sources. The Concept article discusses current benefits and limitations of the technology and its potential to contribute to a more sustainable world. The article shows, for the first time, by the example of an established fermentation process, that there can be realistic economic incentives for using microbial electrochemical technologies for bio‐production. However, it also addresses the many hurdles to be overcome before the depicted "green world" can become reality. More details can be found in the Concept by Harnisch et al. on page 758 (DOI: 10.1002/cssc.201402736).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>